The Role of WhatsApp Interaction in Internalizing Birrul Walidain Values in Students: A Qualitative Approach at Al-Amin Islamic Boarding School, Pabuwaran - Anggraini, Seli; Putra, Robby Aditya (Journal of Engineering and Vocational Education, 2026)
Purpose of the study: This study aims to analyze the role of WhatsApp interaction in the process of internalizing birrul walidain values among santri at Al-Amin Islamic Boarding School Pabuwaran, particularly in conditions of limited face-to-face communication with parents.Methodology: This study uses a descriptive qualitative approach. Data were collected through observation, semi-structured interviews, and documentation. Informants were selected purposively, consisting of female santri and parents. Data sources include primary and secondary data. Data analysis techniques involve data reduction, data display, and conclusion drawing with triangulation for validity.Main Findings: The findings show that WhatsApp interaction significantly supports the internalization of birrul walidain values through routine and open communication. The effects include cognitive (understanding parental advice), affective (emotional closeness and empathy), and conative (obedience and respectful behavior). Digital communication also enables the implementation of religious values despite physical distance.Novelty/Originality of this study: This study integrates digital communication and Islamic values by examining WhatsApp as a medium for internalizing birrul walidain among santri. It offers a contextual perspective within Islamic boarding schools and highlights how religious character formation can occur through digital interaction, contributing to the development of Islamic communication studies in the digital era.